Riesgo de desarrollar diabetes mellitus tipo 2 en la población de la cabecera cantonal de Yantzaza - Castillo Granda, Kevin Kenji (2021)
Type 2 diabetes mellitus (DM2) is a very important public health problem, so it is necessary to focus primary care towards a culture of prevention, reducing modifiable risk factors; and for this, it is possible to carry out a screening by applying the FINDRISC Test. The present study had the purpose of establishing the risk of developing DM2 in the population of the cantonal capital of Yantzaza; identify the level of education, economic activity and cigarette consumption as factors associated with the development of DM2 and develop actions to promote health and prevent this disease. The research had a mixed approach, with a cross-sectional cohort, in which 356 people between 18 and 64 years old residing in the city of Yantzaza, selected in a stratified way by age groups, participated, to which a structured survey and the aforementioned Test were applied. . In the results, there was a predominance of the low and slightly elevated risk score with 88.2%, and a moderate to greater risk of 11.8% of presenting DM2 in the next 10 years. The risk of developing DM2 was shown to be higher in women (18%) than in men (5.6%), and in people between 55 and 64 years of age (35.9%). The level of primary education (16%), people who dedicate themselves to household chores and personal services (21.5%) had a higher prevalence, however, these variables did not represent statistical significance. Cigarette consumption had no influence on the increased risk. Keywords: risk factors, body mass index, cigarette, educational level, economic activity.